DAMPAK MENTAL HECTIC BAGI PERKEMBANGAN EMOSI ANAK PADA MASA PANDEMI COVID-19 DI KABUPATEN PROBOLINGGO - Debby Adelita Febrianti Purnamasari (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
Mental hectic is instability or a disturbance in a person's mental, can be early childhood, adolescents and adults. Mental hectic in children is due to learning activities that are far from the nature of children's learning, namely playing and having fun. Children's emotional development includes recognizing what feelings and emotions they are experiencing, understanding how and why they occur, recognizing their own feelings and those of others, and developing effective ways of managing them. The purpose of this study is to identify the mental hectic that occurs in early childhood. The second goal is to identify children's emotional development. The third objective is to identify the impact of hectic mentality on children's emotional development. The approach used in this research is qualitative phenomenology. The survey was conducted on the child's environment and experiences. The results of this study are the environment around the child is the cause of mental hectic and has an impact on the child's emotional development. Some children aged 3-6 years were identified as experiencing mental hectic which caused poor emotional development. More dominant negative emotions shown by children. Keyword: Mental Hectic, Emotional Development